Sustainable And Green Financing In Uzbekistan: Examine The Growth Of Sustainable Financing Options, Including Green Bonds And ESG Investing Principles, In Uzbekistan's Asset Markets. - Jo’rayev Og’abek (Zien Journals, 2024)
Uzbekistan, a country rich in natural resources and cultural heritage, has been undergoing significant economic and political transformations in recent years. As the country strives to achieve sustainable and inclusive growth, the role of sustainable and green financing has become increasingly crucial. This article will explore the concept of sustainable and green financing, its importance in Uzbekistan, and the opportunities and challenges that lie ahead
Keywords: green financing; economic growth; diversity; challenges